2019
DOI: 10.1111/sms.13418
|View full text |Cite
|
Sign up to set email alerts
|

Sports participation is inversely associated with C‐reactive protein levels in adolescents: ABCD Growth Study

Abstract: Objective To analyze the relationship between sports participation and C‐reactive protein (CRP) levels in adolescents and to identify the possible role of mediation developed by trunk fatness (TF). Methods Cross‐sectional design, part of the longitudinal study entitled “Analysis of Behaviors of Children During Growth” (ABCD Growth Study), Presidente Prudente, SP, Brazil. The sample comprised 259 adolescents (14.7 ± 2.1 [182 boys and 77 girls]) stratified according to sex and engagement in sports in agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…In adolescents, CRP is inversely related to vigorous-intensity levels of PA, showing that exercise may protect against low-grade systemic inflammation in youth ( 48 ). In a recent cross-sectional design, Cayres et al ( 52 ) demonstrated that in adolescents both previous sports participation and regular engagement in PA are inversely related to CRP levels, indicating that frequency and intensity of sports are important factors associated with CRP levels. In line with these observations, we also found that CRP and ESR levels were correlated with several body composition parameters indicative of healthier status, CRP levels were significantly reduced over the study period, while ESR was influenced by either PA or NEP in our adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In adolescents, CRP is inversely related to vigorous-intensity levels of PA, showing that exercise may protect against low-grade systemic inflammation in youth ( 48 ). In a recent cross-sectional design, Cayres et al ( 52 ) demonstrated that in adolescents both previous sports participation and regular engagement in PA are inversely related to CRP levels, indicating that frequency and intensity of sports are important factors associated with CRP levels. In line with these observations, we also found that CRP and ESR levels were correlated with several body composition parameters indicative of healthier status, CRP levels were significantly reduced over the study period, while ESR was influenced by either PA or NEP in our adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the reduction in body fat, through the regulation of energy expenditure, may be an important role, as observed in the present study 15 . In addition, sports practice is associated with reductions in inflammatory levels 30 , through the reduction in some cytokines such as IL-6 and adiponectin 31 , which are, in turn, associated with metabolic syndrome risk 32 . Moreover, intensity seems a key point to determine how effectively sports participation can impact metabolic aspects in adolescents, in which sports performed at higher physical demand tend to be more beneficial to different lipid and glycemic components than those performed at lower demand, including HDL-c 33 .…”
Section: Discussionmentioning
confidence: 99%
“…More details about the sampling process can be found elsewhere [ 20 , 21 ]. In brief, at baseline, researchers contacted adolescents in eleven school units and sports clubs spread out in the metropolitan region of the city.…”
Section: Methodsmentioning
confidence: 99%